SUSTAINABLE FINANCIAL DEVELOPMENT FOR SMALL MEDIUM COFFEE FARMERS IN SUMEDANG REGENCY, INDONESIA - Raden Aswin Rahadi; Yunieta Anny Nainggolan; Kurnia Fajar Afgani; Ima Mulyama Zainuddin; Mia Rosmiati; Aisyah Moulyni; Ainindita (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Coffee is one of Indonesia’s leading export commodities. One of the coffee-producing areas in Indonesia is Sukawangi Village, Sumedang Regency, West Java Province. As the sole actor in running a business, the business actor never calculates the production costs that arise into the cost element. One of the problems of SMEs is the lack of knowledge of SME entrepreneurs about good business management. The next problem faced by SME entrepreneurs is increasing their business competitiveness. Another problem of SMEs that often escapes the attention of UKM entrepreneurs is branding. The last mistake that many UKM players make is that many are not aware that manual bookkeeping is a serious problem for SMEs. In this study, the authors performed a literature synthesis to understand the underlying reasons for issues faced by SMEs about good business management. From the analysis, it can be concluded that consumer behaviour/ preferences/ shops; value chain/ geographical; sustainability/ environment; finance farming; regulation/ certification; and COVID-19 plays a significant part in determining the success of coffee production. Further studies should be performed to test this conceptual model in Indonesia. The results of the study can be useful for all the stakeholders in the coffee Industry, particularly the coffee farmers.